Salesperson Behaviour and Buyer-Seller Relationship Characteristics: An Analysis of Its Impact On Buyer Loyalty in the Malaysian Pharmaceutical Industry - Cheah, Chor Eng (2003)
Today, perhaps more rapidly than any other time in recent history, the business-to business competitive environment is changing (Liu and Leach, 2001). While the preceding statement particularly refers to a business-to-business context, it is not too far-fetched to argue that this observation rings true for other business environments. Driven by concerns over efficiency and effectiveness, many buyers of large firms are reducing the number of suppliers1 they conduct business with and creating more intense relationships with their chosen firms (Geyskens et al., 1998; Napolitano, 1997; Sengupta et al., 1997; Sharma, 1997). These initiatives are mutually reciprocated by suppliers’ proactive role in the development of marketing relationships. In fact, relationship marketing (RM) has been touted as one of the key developments of modern marketing science (Hennig-Thurau, 2000). Such developments are not surprising since studies have shown both suppliers and customers gain the benefits. According to Gummesson (1999), the customer-supplier2 relationship forms the classic dyad of marketing and the relationship forms the parent relationship of marketing. Studies have shown that interpersonal activities at the customer-contact point enable delivery of value-added processes (Humphreys and Williams, 1996). In many industries, salespersons may be the only interface between firms and their customers or prospects, since selling activities are primarily implemented by salespersons. A more recent view of a salesperson by Wotruba (1991) holds that the objective of the salesperson is to build or maintain long-term relationships, and the salesperson is expected to be oriented towards long-term customer needs. Indeed, evidence indicates that salespeople play a central role in the evolution of quality business relationship (Dwyer et al., 1987; Hawes et al., 1989; Crosby et al., 1990). According to Boles et al. (2000), this role orientation is consistent to what is termed relationship selling (RS) behaviours, adding that this role is distinct from the traditional sales process activities such as handling objections and closing since it focuses on the development of dyadic personal relationships between the salesperson and buyer that are mutually beneficial. This leads to the contention that relational characteristics of the buyer-seller relationship and the orientation of the salesperson manifested in the behavioural characteristics of the salespeople will significantly influence the direction and outcomes of a customer-salesperson relationship. In recent years, the term RM has gained prominence in the realm of marketing. Grönroos (1994, 1996) stated that both industrial and modern services marketing approaches clearly view marketing as an interactive process in a social context where relation building and management are vital cornerstones. According to him, RM is ‘to identify and establish, maintain, and enhance relationships with customers and other stakeholders, at a profit, so that the objectives of the parties involved are met. This is done by a mutual exchange and fulfilment of promises’. In a similar vein, Weitz and Bradford (1999) stated that RM could be applied to a number of marketing activities ranging from consumer frequency marketing programs to selling activities directed toward building partnership with key business-to-business customers. In short, RM can be viewed as development of long-term relationship between customers and sellers through sales and marketing activities that focuses on mutual exchanges and promises. The prominence of RM is also evident to the extent that many notable researchers and authors have generally accepted it as representing a paradigm shift in marketing (Kotler, 1990; Parvatiyar et al., 1992; Grönroos, 1994; Morgan and Hunt, 1994; Sheth and Parvatiyar, 1994; Parvatiyar and Sheth, 1997; Gummesson, 1999). Consequently, the study and definition of marketing as an exchange has been expanded to emphasise the relational aspects of buyer-seller interactions with focus on long-term customer satisfaction and value-added selling through the implementation of customer-oriented strategies (Williams, 1998). Given that salesperson behaviours and buyer-seller relationship characteristics significantly influence the outcomes of a customer-salesperson relationship, they are strongly emphasised from a RM perspective. As such, these dimensions have been the subjects of extensive empirical research and literature reviews. In examining the buyer-seller relationship further, Crosby et al. (1990) found that RS behaviours that refer to activities and behaviours that lead to customer relationships are positively linked to sales performance and lower customer turnover. Other outcomes of the RM efforts such as trust and satisfaction have been positively associated with the characteristics of the customer-seller relationships or the salesperson behaviour (Crosby et al., 1990; Doney and Cannon, 1997; Foster and Cadogan, 2000). These characteristics have also been either directly or indirectly (through trust, satisfaction, and salesperson loyalty) linked to customer loyalty behaviours (Crosby et al., 1990; Doney and Cannon, 1997; Foster and Cadogan, 2000; Liu and Leach, 2001). Similarly, the extent of relational contact characterised by frequency of contact and duration of the relationship will influence trust and satisfaction (Lagace et al., 1991). These dimensions are further elaborated in Chapters II and III. In summary, empirical evidence drawn from literature shows that relational selling behavioural characteristics, the characteristics of the buyer-seller interaction itself and the extent of relational contact are major determinants of relationship outcomes. From a commercial perspective, it is indeed crucial to establish and maintain long-term mutually beneficial and successful relationships especially since many buyers of large firms are reducing the number of suppliers they conduct business with and creating more intense relationships with their chosen firms.